Paradigma Pendidikan Muhammadiyah - Najamuddin, Mulyono (Islam Kontemporer, 2016)
Muhammadiyah pioneering in the field of education has been widely recognized and some even say that Islamic organization Muhammadiyah is most concerned with taking care of education. Muhammadiyah is also known to have the most educational institutions, not only at national level, Indonesia, but also throughout the world.Since its inception the organization has concentrated on Islamic movements substantially proselytizing commanding the good and forbidding the evil that contain a broad sense that invites people to Muslim, Islamic straighten Muslims, as well as improving their quality of life intellectually, socially, economically and politically. Organizational management is done in a modern way. Said to be modern for the regeneration of leadership apply on an ongoing basis. In addition, the process does not occur cult, which sees the leadership of the organization as individuals most perfect.Pioneering Muhammadiyah in native education modernization noteworthy with gold ink. While most people are still allergic to the public schools, as synonymous with the Dutch secular, secular groups allergic opposite attitude toward religion. Muhammadiyah succeeded so brilliantly by mating and to combine them in the development of education.